ENGLISH PRE-SERVICE TEACHERS’ ANXIETY IN THEIR TEACHING PRACTICUM DURING COVID-19 PANDEMIC - Mukminatus Zuhriyah; Elisa Nurul Laili (EJI (English Journal of Indragiri) : Studies in Education, Literature, and Linguistics, 2023)
The purpose of this study was to describe the anxiety experienced by English pre-service teachers in their teaching practicum during this COVID-19 pandemic. This study was a descriptive case study. The participants of this study were 28 students from an English language department at a private university in East Java. These students carried out their practice teaching from January 2, up to February 28, 2022. Then, the researcher administered questionnaires in the form of open-ended questions through Google Form to collect the data. In analyzing the data, the researcher used the theory of a-five factor language teachers’ anxiety by Devellis. Meanwhile, the technique of data analysis used was the Miles, Huberman, and Saldana’s theory. The results of this study showed that the five factors of teaching anxiety comprising of inexperience teaching, self-perception of language proficiency, feeling afraid of getting negative evaluation, the students’ less interest in teaching activities, and getting difficulty in their teaching time management, existed. Hopefully, this present study results can be used as the consideration for EFL lecturers in providing some strategies for the future English pre-service teachers to overcome their teaching anxiety.